Prevalence and risk factors of preoperative deep vein thrombosis in elderly patients with hip fractures - Hamid, Mohd Khazran (2020)
Introduction Hip fractures are common in the elderly population after a fall. Consequently, they are at a high risk of developing complications such as venous thromboembolism, deep vein thrombosis (DVT) and pulmonary embolism (PE), which may cause significant morbidity and mortality. To date, there are no local data regarding the prevalence of DVT before surgery in elderly patients with hip fractures and risk factors associated with it. This study aimed to establish the prevalence of DVT in elderly patients following a hip fracture in the local population and evaluate the risk factors for the occurrence of preoperative DVT in this population. Materials and methods This research is a retrospective cross-sectional study involving 91 patients with a history of hip fracture and received treatment in HUSM from January 2014 to November 2019. Patient screening was conducted via the PACS (Picture Archiving and Communication Systems) system and the patients’ medical records. Patients with hip fractures and had ultrasound Doppler of lower limb one day before surgery were selected. All selected risk factors, including demographic data information was then recorded in a study proforma. Data were entered in Microsoft Excel and analysed using SPSS version 26.0. Results The overall prevalence of preoperative deep vein thrombosis in elderly patients with hip fracture was 5.4 %. The mean duration of immobilisation in DVT patient is 18.4 days. None of them received Enoxaparin as prophylaxis. Two out of five DVT patients had underlying malignancy. Conclusion Preoperative DVT prevalence is relatively low (5.4 %) in elderly patients with hip fracture in this study, which may be contributed by precautions taken to prevent DVT in this population. The critical risk factors for DVT development were the duration of immobilisation, types of DVT, prescribed prophylaxis and malignancy.